Chinese Fishes - Noakes, David L. G.; Romero, Aldemaro.; Zhao, Yahui.; Zhou, Yingqi. (Developments in Environmental Biology of Fishes, 2009)
This book documents the current state of research by Chinese scientists on fish biology and fisheries and brings together manuscripts by authors from research institutions, universities and government agencies. There are papers on aquaculture, life history, genetics, marine and freshwater biology, conservation, physiology, new species descriptions, and truly amazing hypogean fishes. The information on these remarkable cave species shows how much we have yet to learn from that incredible fauna. There are papers dealing with some of the largest fishes and some of the smallest cave species. There are papers dealing with some of the most traditional forms of aquaculture and others with the most modern molecular techniques. The volume includes papers on critically threatened native fishes as well as the most common food species, such as grass carp (Ctenopharyngodon idella). The information on rare and threatened species shows how China is dealing with their endangered fishes. The information on their carp species will be invaluable to those in other countries who will either take advantage of the productive carp species in aquaculture or try to manage them as invasive species outside China. For the first time we bring together a complete overview of the state of fisheries research in China.